Male infertility in mice lacking the store-operated Ca2+ channel Orai1. Issue 4 (April 2016) - Davis, Felicity M.; Goulding, Eugenia H.; D'Agostin, Diane M.; Janardhan, Kyathanahalli S.; Cummings, Connie A.; Bird, Gary S.; Eddy, Edward M.; Putney, James W.
Graphical abstract: Highlights: Orai1 knockout male mice are sterile. Mouse testicular cells, including germ cells, have robust store-operated calcium entry, and this is completely lost in Orai1 knockout mice. In the testes of Orai1 knockout mice, mature sperm fail to develop fully or survive. Orai1-mediated Ca 2+ entry appears necessary for the late stages of sperm development. Abstract: Store-operated calcium entry (SOCE) is an important Ca 2+ influx pathway in somatic cells. In addition to maintaining endoplasmic reticulum (ER) Ca 2+ stores, Ca 2+ entry through store-operated channels regulates essential signaling pathways in numerous cell types. Patients with mutations in the store-operated channel subunit ORAI1 exhibit defects in store-operated Ca 2+ influx, along with severe immunodeficiency, congenital myopathy and ectodermal dysplasia. However, little is known about the functional role of ORAI1 in germ cells and reproductive function in mice, or in men, since men with loss-of-function or null mutations in ORAI1 rarely survive to reproductive age. In this study, we investigated the role of ORAI1 in male reproductive function. We reveal that Orai1 −/− male mice are sterile and have severe defects in spermatogenesis, with prominent deficiencies in mid- to late-stage elongating spermatid development. These studies establish an essential in vivo role for store-operated ORAI1 channels in male reproductive function and identify these channels as potential non-steroidal regulators of male fertility.